Effects of metformin on the expression of AMPK and STAT3 in the spinal dorsal horn of rats with neuropathic pain - Ge, Anqi (Mol Med Rep, 2018)
Neuropathic pain (NP) is a frustrating and burdensome problem. Current treatments for NP have unendurable side effects and/or questionable efficacy, and once these therapies are stopped, the symptoms often return. Thus, novel drugs are needed to enhance the effectiveness of treatments for NP. One novel target for pain treatments is adenosine monophosphate-activated protein kinase (AMPK), which regulates a variety of cellular processes, including protein translation, which is considered to be affected in NP. Metformin is a widely available drug that possesses the ability to activate AMPK. The signal transducer and activator of transcription 3 (STAT3) pathway plays an important role in neuroinflammation. The present study investigated the analgesic effect of metformin on NP induced by chronic constriction injury (CCI), and the influence of metformin on the expression of AMPK and STAT3 in the spinal dorsal horn (SDH). In CCI rats, paw withdrawal latencies in response to thermal hyperalgesia were significantly shorter, while phosphorylated (p)-AMPK was expressed at lower levels and p-STAT3 was expressed at higher levels in the SDH. Administering intraperitoneal injections of metformin (200 mg/kg) for 6 successive days activated AMPK and suppressed the expression of p-STAT3, in addition to reversing hyperalgesia. Finally, metformin inhibited the activation of microglia and astrocytes in the SDH, which may explain how it alleviates NP.